This problem has been solved!

Do you need an answer to a question different from the above? Ask your question!

# The Laplace transform y(s) of a function y(t) is defined as, P(s) = [y(t)e dt. If y(t) obeys a differential equation d'y dt then y(s) will be 1 (2+s) (1+s) -+y=et with y(0) = 0 and y'(0) = 0. O 1 O (2-s) (1+s) 1 (2+s) (1-8) 1 (2-s) (1-s)

**Related Book For**

## A First Course in Differential Equations with Modeling Applications

10th edition

Authors: Dennis G. Zill

ISBN: 978-1111827052